الزراعة العربية و تحديات الأمن الغذائي - خلف الله, فهيمة (جامعة الوادي - University of Eloued, 2017)
تعتمد معظم الدول العربية على القطاع الزراعي في توفير المنتجات الغذائية وخلق فرص العمل لفئات واسعة من السكان، بالإضافة إلى مساهمته في توفير العملات الصعبة و بالتالي تمويل برامج التنمية، ويعيق تخلف القطاع الزراعي مسيرة التنمية في القطاعات الأخرى، لهذا فان تنمية هذا القطاع يجب أن تحتل مكانة متميزة في التوجهات التنموية العربية، خاصة بعد تزايد السكان وزيادة الطلب على السلع الغذائية. Most Arab countries depend on the agricultural sector to provide food products and create job opportunities for large segments of the population, in addition to its contribution to the provision of hard currency and thus financing development programs. The agricultural sector is hindering development in other sectors. A prominent place in the Arab development trends, especially after the growing population and increased demand for food commodities
Arab agriculture and the challenges of food security
مقال
Keywords: الأمن الغذائي، الزراعة العربية; Food Security, Arab Agriculture